Analisis Natrium Benzoat pada Saos di Yogyakarta - Siti Fatimah; Dian Wuri Astuti; Ni Putu Ayu Kurniasih (LPPM STIKES Guna Bangsa, 2015)
Background: Preservative can block or slow process of fermentation, acidity and analyzes that cause by microbe. Sodium benzoate is one of organic preservative that easy to dissolve and usually additional with various of ingredients like sauce. Sauce is a fluid that can make food tasty. Sauce can be lasting if add by sodium benzoate. Sodium benzoate as preservative can be dangerous for healthy if out maximum level, and that interested research sodium benzoate. The research purpose to know about sodium benzoate and then determine content level existence on samples of sauce bottle on Beringharjo market in Yogyakarta. Research methods: The research describe sodium benzoate exiztence on sauce and than determine sodium benzoate level on saos. The research object sodium benzoate. Statistical variable in this research is one variable that is the existence and level of sodium benzoate on samples. Method that used for analyzed sodium benzoate in this case is base-acid titration in alkalimetry with two test that is qualitative test and quantitative test. This data is set out in table. Result: The research result by samples is 100% contain sodium benzoate and preservative with high level or out of maksimum level that has been certained and did not fulfill the terms of regulation BPOM Nomor 36 Tahun 2013 is 41,70%. Conclusion: there is sodium benzoate preservative on samples of sauce bottle on Beringharjo market in Yogyakarta with level maximum 7.001,61 mg/kg and level minimun 420,175 mg/kg